ANALISIS PRODUKTIVITAS PERIKANAN BUDIDAYA KARAMBA JARING APUNG (STUDI KASUS DI WADUK CIRATA, KECAMATAN CIRANJANG, KABUPATEN CIANJUR) - Aliyah Zainur Ruhaimah; Asep Agus Handaka Suryana; Atikah Nurhayati; Ine Maulina (Universitas Pattimura, 2025)
The aims of the study was to analysis the level productivity and factors can influence the productivity of aquaculture in KJA of Carp and Tilapia in Cirata Reservoir, Ciranjang District, Cianjur Regency, with a research period from December 2024 - June 2025. The method used in this case study method with a sampling technique using the purposive sampling method. The data collection techniques by interviewing and distributing questionnaires with a total of 60 fish farmers as respondents, then the data obtained were analyzed using both descriptive qualitative and quantitative methods. Factors that influence productivity are analyzed using Multiple Linear Regression. The results of the study showed that the productivity level of aquaculture is seen from the productivity per unit area was 26.31 kg/year/m² and seen from the productivity per unit cost was IDR 20,69 /kg. In addition, result of the financial analysis showed an R/C ratio value of 1.9 which means it is that the cultivation business is profitable. The results of statistical tests show that the factors that can influence the productivity of aquaculture are seed quality, and age of fish farmers while land area, feed and length of experience do not have a significant effect.